Emergence of Hepatitis C Virus Genotype 2c Infection Among Human Immunodeficiency Virus–Infected Men Who Have Sex With Men in Tokyo, Japan. Issue 1 (January 2022) - Okamoto, Koh; Yamada, Norie; Suzuki, Tomohiko; Muramatsu, Takashi; Uemura, Haruka; Gatanaga, Hiroyuki; Kato, Takanobu; Hatakeyama, Shuji
Abstract : Abstract: We report on hepatitis C virus genotype 2c infection in 12 human immunodeficiency virus–infected men who have sex with men in Tokyo, Japan. The uncommon strains from the 12 patients were genetically clustered; they suggested an emerging outbreak in this population at high risk of sexually transmitted infections. Abstract : We report on genetically clustered hepatitis C virus genotype 2c infection in 12 human immunodeficiency virus–infected men who have sex with men in Tokyo, Japan, suggesting an emerging outbreak.Supplemental digital content is available in the text.